Synthesis of thin film composite forward osmosis membrane for improved fouling resistance - Zhang, Jie (2014)
In this study, the objective is to synthesize thin-film composite (TFC) Forward Osmosis (FO) membrane for improved fouling resistance. In order to overcome low permeation flux of existing FO membranes and the fouling issues associated with conventional hydrophobic TFC membrane, hydrophilic surface or bulk modifications were adopted. In this study, the hydrophilicity of the TFC FO membrane is improved by modifying the thin-film selective layer by incorporating hydrophilic PEG into the selective layer. This will reduce the fouling propensity of the FO membrane without causing a decline in membrane performances. Main focuses were made on the method of TFC membrane fabrication, in particular to the fabrication of PES support layer, interfacial polymerization of thin-film polyamide selective layer and the testing of fabricated membranes’ water permeability and porosity. In order to improve on the anti-fouling properties of the TFC membrane, PEG was used in the interfacial polymerization via surface modification to produce TFC membrane with a more hydrophilic surface. Membrane performance tests were conducted, and also compared with commercially available HTI membrane. Membrane characterizations for various membrane fabricated were made by studying SEM micrographs for membrane morphology, contact angle test for membrane hydrophilicity, FTIR tests to confirm presence of PEG within surface layer, AFM tests to observe surface roughness of membrane and membrane porosity tests were also conducted. Results obtained had suggested that PEG embedded into the thin-film selective layer improved the hydrophilicity of the membrane, thereby reducing the fouling propensity of the membrane, as supported by fouling tests results. Further experiments for validations and future studies should include modifications to existing cross-flow FO test cell; studying the effect of PVP concentration on membrane performances; and using an indicative humic acid foulants as feed solution for fouling test over a long experimental period for real representative results.